Ameliorative effect of Aristolochia longa and Aquilariamalaccensison lead acetate inducednephrotoxicityin female rats - DEROUICHE, Samir; GHARBI, Safa; ZEGHIB, Khaoula; KHELEF, Yahia (University of Eloued جامعة الوادي, 2020)
Background:Aquilariamalaccensis And Aristolochia longa are plants used extensively in traditional medicine for the treatment of cancer in several regions in Algeria. We investigate the ameliorative effect of Aristolochia longa and Aquilariamalaccensison kidney toxicity induced by lead in female albino rats. Methods:Twenty five (25) apparently healthy female Wistar rats were randomly divided into five groups of five rats in each: control, Pb, Pb + A. longa (Ar), Pb+ A. malaccensis (Aq), and Pb+Ar+Aq. lead (100 mg/kg b.w) as Pb(C2H3O2)2 added in their drinking water for 75 days. A. longa (rhizome powder at a dose 1% w/w of diet) and A. malaccensis (heartwood powder at a dose 1% w/w of diet) were added to the feed during the last 15 days of lead exposed in the animals. Results:Obtained results revealed that lead treatment caused a significant increase in blood glucose level, serum urea, creatinine and uric acidlevel and in kidneyof MDA level and CAT activity. In contrast, it led to an decrease in the kidneyGST activityand GSH level in rats .Also, the results clearly showed that lead causes alterations of glomerular and tubular structure in comparison with controls.Our results showed that treatment with A. malaccensis and A. longa a partial correction of the previous parameters.The histological observations confirmed the nephroprotection results by the biochemical parameters. Conclusion:Results demonstrated beneficial effects of A. longa and A. malaccensis treatment againacetate lead-induced toxicity and kidney damage in rats
Articale in International Journal of biological and Agricultural Research Vol. 01 N. 02
Keywords: A. longa, A. malaccensis, nephrotoxicity, acetate lead, stress oxidative